Molecular Mechanisms Underlying the Time-dependent Autophagy and Apoptosis Induced by Nutrient Depletion in Multiple Myeloma:a Pilot Study - 刘媛 陈燕 文璐 崔国惠 (Journal of Huazhong University of Science and Technology. Medical sciences, 2012)
This study explored the molecular mechanisms underlying the time-dependent autophagy and apoptosis induced by nutrient depletion in human multiple myeloma cell line RPMI8226 cells.RT-PCR and qRT-PCR were used to evaluate the transcriptional levels of Deptor,JNK1,JNK2,JNK3,Raf-1,p53,p21 and NFκB1 at 0,6,12,18,24 and 48 h after nutrient depletion in RPMI8226 cells.We found that transcriptional levels of Deptor were increased time-dependently at 0,6,12 and 18 h,and then decreased.Its alternation was consistent with autophagy.Transcriptional levels of Raf-1,JNK1,JNK2,p53 and p21 were increased time-dependently at 0,6,12,18,24 and 48 h accompanying with the increase of apoptosis.Transcriptional levels of NFκB1 at 6,12,18,24 and 48 h were decreased as com-pared with 0 h.It was suggested that all the studied signaling molecules were involved in cellular re-sponse to nutrient depletion in RPMI8226 cells.Deptor contributed to autophagy in this process.Raf-1/JNK /p53/p21 pathway may be involved in apoptosis,and NFκB1 may play a possible role in in-hibiting apoptosis.It remained to be studied whether Deptor was involved in both autophagy and apoptosis.